Piceatannol and resveratrol share inhibitory effects on hydrogen peroxide release, monoamine oxidase and lipogenic activities in adipose tissue, but differ in their antilipolytic properties. (25th October 2016) - Les, Francisco; Deleruyelle, Simon; Cassagnes, Laure-Estelle; Boutin, Jean A.; Balogh, Balázs; Arbones-Mainar, José M.; Biron, Simon; Marceau, Picard; Richard, Denis; Nepveu, Françoise; Mauriège, Pascale; Carpéné, Christian
Abstract: Piceatannol is a hydroxylated derivative of resveratrol. While both dietary polyphenols coexist in edible plants and fruits, and share equivalent concentrations in several wines, the influence of piceatannol on adiposity has been less studied than that of resveratrol. Though resveratrol is now recognized to limit fat deposition in various obesity models, the benefit of its dietary supplementation remains under debate regarding human obesity treatment or prevention. The research for more potent resveratrol analogs is therefore still undergoing. This prompted us to compare various effects of piceatannol and resveratrol directly on human adipose tissue (hAT). Hydrogen peroxide release was measured by Amplex Red-based fluorescence in subcutaneous hAT samples from obese patients. Interactions of stilbenes with human amine oxidases and quinone reductase were assessed by radiometric methods, computational docking and electron paramagnetic resonance. Influences on lipogenic and lipolytic activities were compared in mouse adipocytes. Resveratrol and piceatannol inhibited monoamine oxidase (MAO) with respective IC50 of 18.5 and 133.7 μM, but not semicarbazide-sensitive amine oxidase (SSAO) in hAT. For both stilbenes, the docking scores were better for MAO than for SSAO. Piceatannol and resveratrol similarly hampered hydrogen peroxide detection in assays with and without hAT, while they shared pro-oxidant activities when incubated with purified quinone reductase. They exhibited similar dose-dependent inhibition of adipocyte lipogenic activity. Only piceatannol inhibited basal and stimulated lipolysis when incubated at a dose ≥100 μM. Thus, piceatannol exerted on fat cells dose-dependent effects similar to those of resveratrol, except for a stronger antilipolytic action. In this regard, piceatannol should be useful in limiting the lipotoxicity related to obesity when ingested or administered alone – or might hamper the fat mobilization induced by resveratrol when simultaneously administered with it. Graphical abstract: Highlights: Piceatannol is a natural hydroxylated derivative of resveratrol. Piceatannol mimics resveratrol actions in human adipose tissue and mouse adipocytes. Both inhibit hydrogen peroxide release and lipogenesis in adipose tissue. Both inhibit monoamine oxidase (MAO)-dependent oxidation of amines. Only high doses of piceatannol inhibit lipolysis in adipocytes.